Development of a stream flood susceptibility index at the municipal level in mainland Portugal - Santos, Pedro Pinto (2019)
The growing computational capabilities and data availability promotes the development of flood susceptibility methodologies, although there is still field for improvement regarding small-scale flood susceptibility assessment. In this research, after assessing a national stream flood susceptibility (SFS) on a cell-by-cell basis, a municipal representation of SFS was performed to rank the 278 municipalities in mainland Portugal.